Structural Composition of Trees Based on Diameter Class Distribution in a Dipterocarp Forest of Bangladesh - Biswas, Shekhar Ranjan; Misbahu aman, Khaled (Indian Forester, 2006)
This paper describes the tree species composition of Idgaon Forest Reserve under Cox’s Bazar Forest Division of Bangladesh based on tree diameter class distribution. While superior tree species such as Dipterocarpus turbinatus, Dipterocarpus alatus, Swintonia floribunda and Syzygium grande was found to occupy the higher diameter classes, many inferior tree species such as Bursera serrata and Pterospermum acerifolium were found to occupy the lower diameter classes. Lack in recruitment from regeneration of superior tree species may be attributable to the problem caused by human interference. Hence measures towards conservation of superior tree species through encouragement of natural recruitment from regeneration should be adopted while maintaining current trend of natural regeneration for inferior tree species.